The Comparison of Learning Achievement, Analytical Thinking, and Learning Retention Entitled “Thai Proverbs” for Matthayomsuksa 1 between using 4 MAT Learning and Role-Play Approaches - เล็กดี, ดาริณี (RMUTI Journal Humanities and Social Sciences, 2015)
The purposes of this research were (1) To examine an efficiency of the lesson plans entitled “Thai Proverbs” of Matthayomsuksa 1 students between using 4 MAT Learning and the Role-Play Approaches of 80/80 (2) To study an effectiveness index entitled “Thai Proverbs” of Matthayomsuksa 1 students between using 4 MAT Learning and Role-Play Approaches (3) To compare learning achievement and analytical thinking entitled “Thai Proverbs” of Matthayomsuksa 1 students using 4 MAT Learning and the Role Play Approaches between before and after learning. (4) To compare learning achievement, analytical thinking and learning retention entitled “Thai Proverbs” of Matthayomsuksa 1 students between using 4 MAT Learning and Role-Play Approaches. The sample used were 44 of Matthayomsuksa 1/1 and 1/2 students of Chiangyuenwittaya school. The tools used consisted of the lesson plan of 4 MAT Learning and Role-play Approaches, learning achievement test and critical thinking test. The statistics used to analyze the data were percentage, mean, standard deviation, t-test (Dependent Sample) and t-test (Independent Sample). The results were as follows 1. The effectiveness of the lesson plan of using 4 MAT Learning and Role-Play Approaches were 83.24/83.75 and 86.59/88.07. 2. The effectiveness indices of the lesson plan of using 4 MAT Learning and Role-Play Approaches were 0.7839 and 0.8482, Students are making progress in learning increased by 78.39 and 84.82. 3. The learning achievement and critical thinking using 4 MAT Learning and Role- Play Approaches after learning were higher than those of before learning of significance at level 0.01. 4. The learning achievement, critical thinking, and learning retention of Role-Play Approach were higher than using 4 MAT Learning of significance at level 0.01.